LARVICIDAL ACTIVITY AGAINST AEDES AEGYPTI AND ANTIOXIDANT, CYTOTOXIC AND MICROBIOLOGICAL EVALUATION OF THE CRUDE ETHANOLIC EXTRACT OF POGOSTEMON CABLIN BENTH - Santos, Lizandra Lima; Martins, Rosany Lopes; Souza, Heden Robson Monteiro; dos Santos, Janaina Corrêa; Malafaia, Cristine Barbosa; Faustino, Cleidjane Gomes; de Medeiros, Fernando Antônio; Farias, Ana Luzia Ferreira; de Oliveira, Letícia Gomes; Moraes, Edmilson dos Santos; dos Santos, Camila Lima; de Almeida, Sheylla Susan Moreira da Silva (Seven Editora, 2026)
The present work aimed to evaluate the larvicidal, antioxidant, microbiological and cytotoxicity activity of the crude ethanolic extract of Pogostemon cablin (Blanco) Benth leaves. The chemical characterization was performed through staining and staining reactions for the detection of secondary metabolite classes. The larvicidal activity against Aedes aegypti was carried out according to the protocol of the World Health Organization. The antioxidant activity was evaluated by the sequestering ability of 2,2-diphenyl-1-picrylhydrazyl (DPPH). As for the microbiological evaluation, the microplate dilution technique was used against three bacteria, according to the protocol of the Clinical and Laboratory Standards Institute. P. cablin presented as classes of secondary metabolites: steroids and triterpenoids, depsides and depsidones, which in synergy with the other substances potentiated the larvicidal action of the species with an LC50 of 63.91 μg.mL-1 in 24 h. There was no antioxidant activity at the tested concentrations, however, it showed inhibition of bacterial growth against E. coli with MIC of 31.25 μg.mL-1. The extract showed moderate toxic action with LC50 of 257.93 μg.mL-1. Therefore, the P. cablin species showed significant larvicidal potential, with bacteriostatic action, the absence of antioxidant action and moderate toxicity.DOI: https://doi.org/10.56238/sevened2026.008-010